1999
DOI: 10.1164/ajrccm.160.3.9806061
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Proteins A and D in Premature Baboons with Chronic Lung Injury (Bronchopulmonary Dysplasia)

Abstract: Surfactant proteins A and D (SP-A and SP-D) are believed to participate in the pulmonary host defense and the response to lung injury. In order to understand the effects of prematurity and lung injury on these proteins, we measured the amounts of SP-A and SP-D and their mRNAs in three groups of animals: (1) nonventilated premature baboon fetuses; (2) neonatal baboons delivered prematurely at 140 d gestation age (ga) and ventilated with PRN O(2); (3) animals of the same age ventilated with 100% O(2) to induce c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
60
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 31 publications
3
60
1
Order By: Relevance
“…However, increased mRNA did not always correlate with increased protein in lavage (54). Increased mRNA for Sftpa, Sftpb, Sftpc, and Sftpd is seen in newborn rats exposed to 85% oxygen (55).…”
Section: Discussionmentioning
confidence: 81%
“…However, increased mRNA did not always correlate with increased protein in lavage (54). Increased mRNA for Sftpa, Sftpb, Sftpc, and Sftpd is seen in newborn rats exposed to 85% oxygen (55).…”
Section: Discussionmentioning
confidence: 81%
“…The SP-A content of BALF has been shown to vary in individuals with various lung diseases (3)(4)(5). Moreover, qualitative and quantitative differences have been observed in vitro between the SP-A1 and SP-A2 genes (22,36,57,60,(77)(78)(79)(80)(81), pointing to the possibility that the overall functional activity of SP-A may depend on the relative SP-A1-to-SP-A2 levels rather than on the total SP-A content.…”
Section: Discussionmentioning
confidence: 99%
“…More than 30 alleles have been characterized for these two genes, with four SP-A1 alleles (6A, 6A 2 , 6A 3 , and 6A 4 ) and six SP-A2 alleles (1A, 1A 0 , 1A 1 , 1A 2 , 1A 3 , and 1A 5 ) most frequently observed in the general population (10,14,16,40,67). Although a high level of sequence similarity is shared among the SP-A genes and their corresponding alleles, in vitro studies have identified both qualitative (22,36,57,60,77,80,81) and quantitative (24,35,38,46,56,69,70,78,79) differences between the two genes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that a pro re nata (PRN) approach to oxygen therapy at 140 days of gestation (a relatively more mature preterm infant) allowed for complete recovery from HMD and was not accompanied by clinical, radiographic, and pathological manifestations of BPD. Subsequent studies demonstrated that postnatal infection, related to endotracheal instillation of gram-negative bacteria, and/or abnormal surfactant protein A (SP-A) metabolism were important cofactors in BPD morbidity of the 140-day model (5,21).…”
Section: -Day Model ("Old Bpd")mentioning
confidence: 99%